The effect of forage legume supplementation on digestibility and body weight gain by sheep fed a basal diet of maize stover - Getachew, G.; Said, A.N.; Sundstol, F. (Elsevier, 1994)
Growth and digestibility experiments were conducted with Ethiopian highland sheep offered a maize stover basal diet and supplemented with one of the three legume hays (Desmodium intortum, Macrotyloma axillare and Stylosanthes guianensis), legume hay plus cottonseed cake, and cottonseed cake alone, to investigate feed intake, digestibility and body weight change, sheep in the M. axillare supplemented group recorded higher dry matter and nitrogen intake, and showed a higher gain in body weight. When legumes were given in combination with cottonseed cake, intortum and M. axillare supplemented group recorded higher dry matter and nitrogen intake, and showed a higher gain in body weight. When legumes were given in combination with cottonseed cake, intortum and M. axillare supplemented sheep recorded similar body weight gains. S. guianensis supplemented sheep lost weight during the first phase and showed relatively low body weight gains during the second phase. Legumes fed together with cottonseed cake as a supplement to maize stover increased digestibility of most dietary soluble and cell-wall constituents compared with legumes supplements alone.